Evaluation of climate change effects on rain rate distribution in Malaysia using hydro-estimator for 5G and microwave links - Basarudin, Hafiz; Mohd Yunus, Noor Hidayah; Ramli, Aizat Faiz; Mansor, Zuhanis; Sali, Aduwati; Hong Seng, Gan; Abu, Mohd Azlan (Engineering Technology and Applied Science Research, 2023)
Wireless transmissions at more than 10GHz can experience signal fading caused by the presence of hydrometeor particles in the atmosphere. Among these hydrometeors, rain is the largest contributor to the fading mechanism. Rain fade can be predicted or calculated using rain rate measurements. With climate change affecting the world due to the rise of carbon dioxide in the air, it is expected to affect the distribution of rainfall, which ultimately affects rain fade. This paper investigates the effects of climate change on rain rate distribution in Malaysia. Ten years of Hydro-Estimator data containing rainfall rates in Peninsular Malaysia and the Sabah and Sarawak region from 2011 to 2020 were collected and analyzed. Using the linear regression method, a small increment of rain rate distribution at 0.01 annual probability was detected for all regions, indicating a climate change effect on the rain rate distribution. For Peninsular Malaysia, the rate was 0.2356mm/hr per year while for the Sabah and Sarawak region, it was 0.4046mm/hr per year. An increase in the rain rate would increase the rain fade, causing signal losses and distortions in high-frequency wireless communication signals. The evaluation of climate change effects on the rain rate and rain fade distributions can help in developing a long-term prediction of the signal performance in 5G systems and high-frequency radio link frequencies due to hydrometeors.